Self Care Behaviors in Diabetic Patients Referring to Diabetes Clinics in Babol City, Iran - SR Jafarian Amiri (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Nowadays diabetes is a main public health problem in the world that needs patients cooperating in the therapeutic process and diabetic patient has central role in its management. The aim of this study was to assess self care behaviors and its related factors in diabetic patients.METHODS: This cross-sectional study was done on 201 diabetic patients referring to diabetes clinics of Babol town who were selected by easy sampling method. Data was collected by means of SDSCA (Summary of Diabetes Self Care Activities) questionnaire (score range 0-105) consists of two parts of demographic characteristics ( age, sex, height, weight, education, job, marital status, etc) and self care behaviors questions ( medication, diet, exercise, self monitoring of blood glucose and foot care). FINDINGS: In this study 166 females (82.6%) and 35 men (17.4%) participated. The mean age of participants was 50.61±11.1. Most of patients were housewives 151 (75.1%) and married 174 (86.6%). Eighty-three (41.3%) of patients didn’t have suitable diet and only 47 (23.4%) of them had suitable diet during the week. Also 59 (29.4%) of them didn’t have prescribed physical activity last week, 152 (75.6%) of patients didn’t check their blood sugar according to their recommended plan and 66 (32.8%) of them checked their blood sugar only once a week. In this study, patients with higher educational level had better foot care (p=0.000) and physical activity (p=0.02). Findings showed that patients who had better self care behaviors had lower FBS results (p=0.000) and BMI (p=0.01). CONCLUSION: According to the results of this study, attention should be given more to illiterate or low educated persons and there should be proper teaching program to increase self care behaviors.